Cysteine, Malondyaldehide (MDA) and Glutathione (GSH) Levels in Marasmic Type Malnutrition - Dwi Indah Cahyani; Anik Puryatni; Nur Permatasari (Journal of Tropical Life Science, 2017)
Micronutrien deficiency in severe malnutrition will reduce antioxidant capacity that needed for oxidative stress defense. Cysteine, a non-essential amino acid, is one of an important component for reduced glutha-tione (GSH). This study aims to prove the difference between the levels of cysteine, MDA and GSH levels in children with marasmic malnutrition and well-nourished children and prove whether there is a relationship between those parameters. Fiftysix patients participated in this study were grouped into two groups of sam-ples that were marasmic type malnutrition group (28 patients) and control groups that were well nourished group (28 patients). Examination begins with a complete laboratory screening, followed by examination of cysteine, MDA and GSH level. Of the 28 patients included in marasmic type malnutrition group consisting of 15 male patients (53.6%) and 13 female patients (46.4%), while the well-nourished group consisted of 13 male patients (46.4%) and 15 female patients (53.6%). The average age is 54.61Â±56.35 months in the group of ma-rasmic type malnutrition and 48.25Â±45.34 months in the well-nourished group. By using the Mann Whitney test, there were significant difference between the levels of cysteine and GSH in marasmic malnutrition and control group (p = 0.000 and p = 0.000 respectively). Spearman correlation test between cysteine and GSH levels, cysteine and MDA levels, MDA and GSH levels in marasmic malnutrition children shows no significant correlation (R = -0.206, p = 0.294; R = -0.036, p = 0.856; R = 0.210, p = 0.284 respectively). In well-nourished group Spearman correlation test between cysteine and GSH levels, cysteine and MDA levels, MDA and GSH levels also shows no significant correlation (R = -0.053, p=0.789; R = -0.146, p = 0.458; R = -0.079, p = 0.688 re-spectively). From this study it can be concluded that there are significant differences of the levels of cysteine and GSH between severe malnutrition groups compared with the control one. But this study shows no signif-icant correlation between the levels of cysteine and GSH levels in marasmic type malnutrition and well-nourished children.